Job Satisfaction of Employees in Commercial Banks - Pathak, Hari Prasad (Journal of Nepalese Business Studies, 2016)
This paper analyzes the level of job satisfaction among employees of commercial banks along with the consideration of gender, age and experience differences. Four commercial banks were selected using purposive sampling method for the study. Further, a total of 260 respondents were selected randomly from the four banks’ head offices and branch offices located in Kathmandu Metropolis. The modified Minnesota Satisfaction Questionnaire (MSQ) was used to gather data about the job satisfaction of respondents. The results indicate that almost 66% of employees are satisfied or highly satisfied with their jobs. Job security’is the most significant factor of job satisfaction to the employees of commercial banks in Nepal. Level of job satisfaction does not differ significantly between male and female employees. However, there are significant differences in level of job satisfaction among various age groups of employees. Journal of Nepalese Business Studies Vol. 9, No. 1, 2015 pp. 63-76